The Development of a High-Efficiency Small Induction Furnace for a Glass Souvenir Production Process Using Multiphysics - Thongsri, Jatuporn; Poopanya, Piyawong; Sriphalang, Sanguansak; Pattanapichai, Sorathorn (My University, 2024)
A small induction furnace (SIF), which has the important components of copper coils, a ceramic jig, and a graphite crucible, employed for a glass souvenir production process, has been developed as a form of clean technology for multiphysics, consisting of electromagnetics analysis (EA) and thermal analysis (TA). First, two experiments were established to measure parameters for multiphysics results validation and boundary condition settings. Then, the parameters were applied to multiphysics, in which the EA revealed magnetic flux density (B) and ohmic losses, and the TA reported a temperature consistent with the experimental results, confirming the multiphysics credibility. Next, a ferrite flux concentrator was added to the SIF during development. Multiphysics revealed that PC40 ferrite, as a flux concentrator with a suitable design, could increase B by about 159% compared to the conventional SIF at the power of 1000 W. As expected, the B increases alongside the increase in power applied to the coils, and is more densely concentrated in the flux concentrator than in other regions, enhancing the production process efficacy. Lastly, the developed SIF was employed in the actual process and received good feedback from users. The novel research findings are the developed SIF and methodology, exclusively designed for this research and practically employed for a glass souvenir production process.
Keywords: ANSYS Maxwell; clean technology; finite element analysis; glass souvenir; heat transfer; induction heating; magnetic flux concentrator; multiphysics; SDGs; sustainable development goals; thermal simulation; thermochromic dye